2021
DOI: 10.1002/ldr.3889
|View full text |Cite
|
Sign up to set email alerts
|

The divergent impact of phenology change on the productivity of alpine grassland due to different timing of drought on the Tibetan Plateau

Abstract: Droughts are predicted to become more frequent and persist for longer periods in the future, especially in alpine regions due to climate change. However, the association mechanism between plant productivity response to drought timing and phenology in the alpine grassland of the Tibetan Plateau is unclear. We conducted manipulative drought experiments on early growing season drought (ED) and middle growing season drought (MD) to determine the impacts of drought timing on the alpine grassland. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, in a semi-arid alpine meadow in the central QTP, delay in SOS induced by manipulative water stress depressed GPP, biomass, and net ecosystem production 117,171 . As expected, the effects of spring phenology on biomass are species-specific and complex 141,172 .…”
Section: Ecosystem Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a semi-arid alpine meadow in the central QTP, delay in SOS induced by manipulative water stress depressed GPP, biomass, and net ecosystem production 117,171 . As expected, the effects of spring phenology on biomass are species-specific and complex 141,172 .…”
Section: Ecosystem Functioningmentioning
confidence: 99%
“…However, note that statistical correlations between the timings of spring or autumn events and ecosystem parameters (such as biomass or GPP) integrated over months do not necessarily quantify the exact contributions of phenological changes to those ecosystem structures and functions. Quantification of these contributions would be more complicated when considering the potential indirect effects of phenological changes on alpine ecosystems through interactions with other environmental factors 141,171,174,175 .…”
Section: Ecosystem Functioningmentioning
confidence: 99%
“…The estimation of LCC S and ASR S is based on the mechanisms displayed in Figure 3. The POS was determined by the joint effects of plant growth and grazing activity [30,49]. Conversely, the POS can be used to reflect the grazing severity through plant growth function as shown in Equations ( 18) and (19).…”
Section: The Estimation Of Lcc and Asrmentioning
confidence: 99%
“…Although temperature was regarded as the primary climatic factor controlling the plant spring phenology [52], the in situ species-level observations [28] and manipulative experiment [16] in alpine meadow on the QTP have demonstrated that soil moisture is also important in controlling green-up onset of alpine grassland on the QTP [28,53]. With the decrease in the soil moisture in spring, the green-up of the vegetation community was significantly delayed as the drought was induced [54]. Snowmelt is the only source of soil water in winter [28] in many areas of the QTP.…”
Section: The Role Of Snowfall In Driving Alpine Grassland Spring Phen...mentioning
confidence: 99%